(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Throughout this century there have been witnessed to considerable changes in people’s lives. One conspecious example of this can be seen escalation of technology. According to perspectives of vast majority technology is a tool and it is utilized as a matter of putting down the gaming system, tablet, or phone while others claim that technology addiction is real and it demands medical treatment. As per my opinion this dependency have some negative influence too.